PEMANFAATAN LIMBAH HUTAN TANAMAN INDUSTRI (HTI) MENJADI PUPUK CAIR ORGANIK DAN APLIKASINYA PADA TANAMAN AKASIA MANGIUM (Acacia mangium Willd.) - Idris, Rahmad; Sulaeman, Rudianda; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The amount of waste generated logging plantation forests (HTI) come to the surface environmental impacts, whereas the waste can still function to use and processed into smoke liquid. Smoke liquid products was made from logging waste (HTI) can be used as an alternative to artificial fertilizers or chemicals. The purpose of this study was to evaluate the response of the acacia plants growth by administering smoke liquid. The benefits of this research is to develop the use of smoke liquid as a natural liquid fertilizers, find how to use smoke liquid as a natural fertilizers for the public plant acacia. Increase the economic value and was usability of waste industrial timber estates (HTI). This study uses a was completely randomized design (RAL) with 4 treatments 3 replications, in order to obtain 120 units of plants with each trial consisted of 10 plants. Results from the study can be showed that administration of smoke liquid affect the growth of plants Acacia mangium Willd. Treatment with a dose of smoke liquid 5 ml / 1 L of the water shows the most optimal response to plant growth compared to treatment with a dose of smoke liquid 1 ml / 1 L of the water and 3 ml / 1 L of water. Giving liquid smoke on the best dose may increase as height, diameter and dry weight of seedlings Acacia mangium Willd. Keywords: Acacia mangium, Utilization, Smoke liquid, Waste industrial forest plantations (HTI)